Специфіка суб’єктного складу у переддоговірній відповідальності закладів охорони здоров’я перед пацієнтом - Ходєєва, Н. В.; Khodeeva, N. V. (Право і суспільство. - 2023. - № 3. - С. 146-150, 2023)
Досліджено специфіку суб’єктного складу в переддоговірній відповідальності яка виникає у закладів охорони здоров’я саме перед пацієнтом. Визначено особливості переддоговірної відповідальності яка виникає між закладами охорони здоров’я та пацієнтами як такої, що може бути як договірною, так і деліктною. Проаналізовано момент набуття фізичною особою статусу пацієнта на всіх стадіях відносин які виникають з медичною організацією, в загалом і на переддоговірній.

The article examines the specificity of the subject structure in the pre-contractual responsibility of health care institutions to the patient. The grounds, conditions and specific features inherent in the pre-contractual responsibility that arises between health care institutions and patients are determined. The peculiarities of pre-contractual liability arising between health care institutions and patients as such, which can be both contractual and tortious, are determined. The moment when an individual acquires the status of a patient at all stages of relations with a medical organization, including the pre-contractual one, is analyzed. It is noted that in a number of cases provided for by the current legislation of Ukraine, rights are granted not only to patients, but also to other persons who, as a result of granting them such a right, do not make them victims: such persons cannot be harmed, taking into account the fact that patients should be considered adults, as well as incapacitated persons and persons with incomplete civil legal capacity. It was determined that the subject of pre-contractual liability can be both a health care institution and an individual – an entrepreneur, whose employees (citizens under a civil law contract) violated pre-contractual obligations. It is respected that it does not add significant respect to the importance of an informed philanthropic cause: the pledges of protecting health are not in the new world of roses to explain to the patient all the arrangements for this possible medical training, as a result of which the patient himself if you sign it yourself, please, don’t turn it over its essence, but as a last resort, the very moment of clarification of the problem or without intermediary s the very glance or the primary consultation, otherwise she hopes not to be completely obligated by the practitioner of the registry, but only formally signed. The possibility of the existence of multiple persons on the side of the health care institution was established, and as a result, the possibility of joint or joint liability.

Исследована специфика субъектного состава в преддоговорной ответственности, которая возникает у учреждений здравоохранения именно перед пациентом. Определены особенности преддоговорной ответственности, возникающей между учреждениями здравоохранения и пациентами как таковой, которая может быть как договорной, так и деликтной. Проанализирован момент приобретения физическим лицом статуса пациента на всех стадиях отношений, возникающих с медицинской организацией, в целом и на преддоговорной.
The specifics of the subject structure in the pre-contractual responsibility of health care institutions to the patient
Keywords: переддоговірна відповідальність; pre-contractual liability; преддоговорная ответственность; суб’єктний склад; subject composition; субъектный состав; заклади охорони здоров’я; health care institutions; заведения здравоохранения; пацієнт; patient; пациент